National multicentre audit of pregnancy status in general surgery admissions in Scotland. Issue 1102 (17th January 2017) - Wilson, Michael S J; Powell-Bowns, Matilda; Robertson, Andrew G; Luhmann, Andreas; Richards, Colin H; ,; Hurley, Rhona; El-Medany, Ahmed; Inwood, Claire-Louise; Mason, Saskia; Gillan, Angela S; Williams, Susan; et al.
ABSTRACT: Background: Documentation of pregnancy status (PS) is an integral component of the assessment of women of reproductive age when admitted to hospital. Our aim was to determine how accurately PS was documented in a multicentre audit of female admissions to general surgery. Methods: A prospective multicentre audit of elective and emergency admissions was performed in 18 Scottish centres between 08:00 on 11 May 2015 and 07:59 on 25 May 2015. The lower age limit was the minimum age for admission to the adult surgical ward and the upper age limit was 55 years. Results: There were 2743 admissions, with 612 (22.3%) women of reproductive age. After 82 exclusions, the final total was 530: 169 (31.9%) elective and 361 (68.1%) emergency. Documentation of PS was achieved in 274 (51.7%) cases: 52 (30.8%) elective and 222 (61.5%) emergency. In 318 (88.1%) of the emergency admissions, the patient had abdominal pain. Of these, 211 (65.1%) had a documented PS. The possibility of pregnancy was established in 237 (44.7%) cases. Discussion: Establishing the possibility of pregnancy before surgery is poor, particularly in the elective setting. Objective documentation of PS in the emergency setting in those with abdominal pain is also poor. Our study highlights an important safety issue in the management of female patients. We advocate electronic storage of pregnancy test results and new guidelines to cover both elective and emergency surgery. PS should form part of the pre-theatre safety brief and checklist.